Expanding the clinical picture of the MECP2 Duplication syndrome. Issue 4 (21st July 2016) - Lim, Z.; Downs, J.; Wong, K.; Ellaway, C.; Leonard, H.
Abstract : Individuals with two or more copies of the MECP2 gene, located at Xq28, share clinical features and a distinct facial phenotype known as MECP2 Duplication syndrome. We have examined perinatal characteristics, early childhood development and medical co‐morbidities in this disorder. The International Rett Syndrome Phenotype Database (InterRett), which collects information from caregivers and clinicians on individuals with Rett syndrome and MECP2 associated disorders, was used as the data source. Data were available on 56 cases (49 males and 7 females) with MECP2 Duplication syndrome. Median age at ascertainment was 7.9 years (range: 1.2–37.6 years) and at diagnosis 3.0 years (range: 3 weeks–37 years). Less than a third (29%) learned to walk. Speech deterioration was reported in 34% and only 20% used word approximations or better at ascertainment. Over half (55%) had been hospitalised for respiratory infections in the first 2 years of life. Just under half (44%) had seizures, occurring daily in nearly half of this group. The majority (89%) had gastrointestinal problems and a third had a gastrostomy. Following the recent demonstration of phenotype reversal in a mouse model of MECP2 Duplication, a clear understanding of the natural history is crucial to the design and implementation of future therapeutic strategies. Abstract :